Impact of mutual interaction between civil society and conditionality by an external actor on democratization: Cases of Turkey and Malaysia - İrem Askar Karakır; Asmady Idris (DergiPark Akademik, 2016)
With their functioning democracies albeit accompanied by various deficiencies, Turkey and Malaysia are often referred to as models in the Islamic world. This study aims to assess progresses and setbacks in democratization in Turkey and Malaysia since the early 2000s with a particular attention to their civil societies and conditionality by an external actor. In Turkey, civil society has had a positive impact on democratic consolidation through encouraging political reforms in line with the EU accession process. In addition, AKP government was highly motivated by EU conditionality in adopting remarkable political reforms particularly in its early years in power. Malaysian civil society has also played an effective role in voicing demands for democratic values as long as shared concerns enabled it to transcend ethnic and religious boundaries. Yet, democracy promotion through conditionality has not existed in Malaysia’s relationship with the ASEAN. It is argued that Turkey has had a more favorable internal and external environment to encourage democratization compared with that of Malaysia.